2020
DOI: 10.2991/chi.d.200221.001
|View full text |Cite
|
Sign up to set email alerts
|

The CD34+ Cell Dose Matters in Hematopoietic Stem Cell Transplantation with Peripheral Blood Stem Cells from Sibling Donors

Abstract: A B S T R A C TThe effect of CD34 + cell dose in allogeneic hematopoietic stem cell transplantation (HSCT) on overall survival (OS) and incidence of acute and chronic graft-versus-host disease (GvHD) has not been established and few studies have been performed. Our single center analysis included 189 patients with hematological malignancies who received peripheral blood stem cell (PBSC) grafts from sibling donors. Myeloablative conditioning was used in 88 cases and 101 received reduced intensity conditioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A single-centre analysis done in Oslo which studied 189 PBSC recipients from sibling donors concluded that a CD34 cell dose of 6-7 × 10 6 /kg showed better survival and lesser mortality while a dose of <5 × 10 6 /kg had increased relapse but lower GVHD and higher than 6.5 × 10 6 /kg had lower acute GVHD. [10] Another study done in 2015 done in 205 patients from a single institution concluded that there is no ideal cell dose at transplant within a range of 10 4 -10 5 . [11] Thus, it becomes very important to define the minimum cell dose required to give the best engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…A single-centre analysis done in Oslo which studied 189 PBSC recipients from sibling donors concluded that a CD34 cell dose of 6-7 × 10 6 /kg showed better survival and lesser mortality while a dose of <5 × 10 6 /kg had increased relapse but lower GVHD and higher than 6.5 × 10 6 /kg had lower acute GVHD. [10] Another study done in 2015 done in 205 patients from a single institution concluded that there is no ideal cell dose at transplant within a range of 10 4 -10 5 . [11] Thus, it becomes very important to define the minimum cell dose required to give the best engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Bickford et al (2006) reported that these agents (as well as catechin) synergistically stimulated the in vitro proliferation of human bone marrow and human CD34 + and CD133+ cells. CD34 + are often used clinically to quantify H-SC numbers in H-SC transplantation ( Remberger et al, 2020 ). CD133 is a well-characterized biomarker of normal and cancer SCs ( Barzegar Behrooz et al, 2019 ).…”
Section: Clinical Trials With Sc Preparations For Agingmentioning
confidence: 99%
“…The remaining 40% of donors usually achieve target yield after repeat PBSC, although 2-5% are poor mobilisers and never achieve target. For recipients, suboptimal CD34 + cell yields from donors result in prolonged engraftment times and increased risk of adverse events such as graft failure, infection, or bleeding (3, 4).…”
Section: Introductionmentioning
confidence: 99%